Model Promosi Nonpendas melalui Reach Approach sebagai Upaya Meningkatkan Mahasiswa Baru - Malik, Abdul; Prasetya, Agus (Widya Warta, 2013)
Promotion  is  an  activity  to  offer  goods  and  services  produced  by  an  institution, factory, or company in order to be recognized by the public. Related to Open University, this promotion will persuade the public to improve their labour productivity by joining Open University. One of promotion methods used is Reach Approach Communication (respect, empathy, audible, clarity, and humble). The  decrease  of  students  can  be  caused  by  less  promotion  in  regions,  especially Madiun regency. The main purpose of promotion is persuading the customers so they will recognize, be interested in, and finally use the product. While, mixed promotion means a promotion with various kinds of way in order to make the people customers. This research is aimed to offer an effective method of promotion so as to increase the new students participation number (APM). This research is qualitative in nature and the source of data is civil servants, students, education observers, and teachers in Madiun. The data  were  collected  through  interviews,  and  documents.  The  data  analysis  was  done  by making use of Huberman and Miles’ analysis method. The analysis showed that there was an increase of 80% of Non Pendas students in Madiun as the effect of the application of the mixed promotion Reach Approach.